(untitled) (Faridpur Medical College Journal, 2017)
Vitiligo is an acquired, often progressive disorder of hypopigmentation. A lot of research has been conducted during the years yet its exact etiology still remains elusive. As a result even after so many years, there is no ideal treatment for vitiligo. Treatment options such as Narrowband Ultraviolet B (NB-UVB), Targeted Phototherapy, and Excimer laser on the medical front, in addition to epidermal cell transplantation and melanocyte culture transplants on the surgical front, have all revolutionized the management of this psychologically devastating disease. Faridpur Med. Coll. J. Jan 2017;12(1): 34-39